DEVELOPING ENGLISH READING TEXT MATERIAL FOR STUDENTS IN SMK NEGERI 10 MEDAN - Geby Cindy F.Sitanggang and Busmin Gurning (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2017)
This study concerns on how reading text material are developed for vocational school. This study was conducted by using Research and Development (R & D) design through six phases; gathering information and data, analyzing data, designing new materials, validating by experts, revising, and final product. The subject of this research was class XI SMK N 10 Medan consisting of 22 students. Instrumentations for collecting data were questionnaire and interview. After analyzing the data, the researcher got the students’ need in learning English in term of vocation that they have. The data were gathered by administering interview and distributing questionnaire to 25 respondents to get the students’ needs. The interview and questionnaire results prove that the students need English reading materials which contain English for cosmetology major. Thus, developing materials were procedure text. The developed teaching material were related to the vocation that the students had; it was beauty major. The products have been validated by experts. The average scores are 4,25 from English subject teacher and 4,17 English lecturer. It means the developing materials categorized as relevant or appropriate for students of beauty major grade XI.